2009
DOI: 10.1007/s12017-009-8091-0
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease Amyloid β-Protein and Synaptic Function

Abstract: Alzheimer's disease (AD) is characterized neuropathologically by the deposition of different forms of amyloid beta-protein (A beta) including variable amounts of soluble species that correlate with severity of dementia. The extent of synaptic loss in the brain provides the best morphological correlate of cognitive impairment in clinical AD. Animal research on the pathophysiology of AD has therefore focussed on how soluble A beta disrupts synaptic mechanisms in vulnerable brain regions such as the hippocampus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
94
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 179 publications
2
94
0
1
Order By: Relevance
“…One of the earliest papers reported that central administration of A inhibited LTP in area CA1 of the hippocampus (Cullen et al, 1997) and this observation was followed by several others which indicated that synthetic and naturally-occurring A oligomers, including A-derived diffusible ligands, inhibited LTP in all major afferent pathways in the hippocampus both in vivo and in vitro (Koffie et al, 2011;Ondrejcak et al, 2010;Walsh et al, 2002).…”
Section: A Inhibits Ltpmentioning
confidence: 97%
“…One of the earliest papers reported that central administration of A inhibited LTP in area CA1 of the hippocampus (Cullen et al, 1997) and this observation was followed by several others which indicated that synthetic and naturally-occurring A oligomers, including A-derived diffusible ligands, inhibited LTP in all major afferent pathways in the hippocampus both in vivo and in vitro (Koffie et al, 2011;Ondrejcak et al, 2010;Walsh et al, 2002).…”
Section: A Inhibits Ltpmentioning
confidence: 97%
“…Although the neuropathological hallmark plaques are composed largely of fibrillar Ab, most attention has been devoted to investigating the pathophysiological role of non-fibrillar, water-soluble forms of Ab [5,6]. Considerable progress has been achieved in elucidating the disruptive actions of soluble Ab on synaptic transmission and plasticity of that transmission [7][8][9]. Extensive studies have examined how endogenous factors influence the time course and extent of the disruption of synaptic plasticity by soluble Ab, with particular emphasis on the actions of putative 'synaptotoxic' assemblies ranging from small oligomers to relatively large protofibrils.…”
Section: Introductionmentioning
confidence: 99%
“…Activity-dependent changes in the efficacy of synaptic transmission within the hippocampus are thought to be required for particular forms of memory, and interference with these changes, caused by elevated levels of Aβ, is thought to contribute to AD-associated memory impairments (31). Because PME-1 overexpression enhances Aβ-induced memory impairments, we sought to determine whether PME-1 overexpression also might enhance Aβ-induced impairment of activity-dependent synaptic plasticity.…”
mentioning
confidence: 99%